PENGARUH KONSELING MENYUSUI KEPADA PASUTRI TERHADAP PENGETAHUAN, DUKUNGAN, DAN KETERAMPILAN TEKNIK MENYUSUI - Pri Hastuti; Endang Sutedja; Dzulﬁkar DLH; Astuti Eka; Lastri Lastri; Lenni Marliza (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Latar belakang: Cakupan ASI eksklusif di Kota Jogja rendah 40,24%, sementara target nasional 80%. Banyak faktor yang mempengaruhi keberhasilan ASI eksklusif, antara lain pengetahuan ibu, dukungan suami dan keter- ampilan teknik menyusui. Upaya meningkatkan cakupannya adalah dengan memberikan konseling menyusui pada pasutri. Dukungan suami berpengaruh terhadap keberhasilan teknik menyusui.Tujuan: untuk mengetahui pengaruh konseling menyusui pada pasutri terhadap pengetahuan, dukungan, dan ke- terampilan teknik menyusui serta korelasi pengetahuan suami dengan istri di kelompok pasutri.Metode: Penelitian ini merupakan penelitian Quasi Eksperiment yaitu menilai “Pengaruh Konseling Menyusui Pada Pasutri Terhadap Pengetahuan, Dukungan dan Keterampilan Teknik Menyusui Di Puskesmas Kota Yogyakarta”, dengan rancangan pretest-posttest control group design. Pengambilan Sampel dengan teknik consecutive sam- pling di puskesmas Jetis,Tegal Rejo, dan Mergangsan, sampel adalah suami dan ibu nifas primipara yang me- nyusui bayinya sebesar 60, teknik randomisasi blok digunakan untuk membagi ke dalam kelompok perlakuan dan control masing masing kelompok 30 sampel. Variabel pengetahuan diukur dengan kuesioner sebelum dan sesudah konseling. Variabel dukungan suami dengan kuesioner sesudah konseling, sedangkan variabel keterampilan me- nyusui diamati dengan daftar tilik menyusui sebelum dan sesudah konseling. Analisa data menggunakan Wilcoxon,Man Whitney dan Rank Spearman.Hasil: penelitian menunjukkan skor pengetahuan dan keterampilan pada kelompok pasutri dan kelompok sendiri.ABSTRACTBackground: Percentage of exclusive breastfeeding in Jogja is low at 40.24 % , while the national target is 80 % . Many factors inﬂuence the success of exclusive breastfeeding, such as knowlwdge skills and techniques in breas- feeding and husband support. Efforts to increase the percentage is to provide breastfeeding counseling to couples. Husband’s support leads to successful breastfeeding techniques.Objective: The purpose of this study was to determine the effect of breastfeeding on couples counseling to the knowledge, support, and technical skills as well as the correlation of the couples knowledge of breastfeeding in a group of couples.Method: This research is a quasi experiment that assesses “ Effect of Breastfeeding Counseling In A married couple on Knowledge, skills technical Support to Breastfeeding In Public Health Centers of Yogyakarta “, by pretest-posttest control group. Sampling with consecutive sampling techniques in health centers Jetis, Tegalrejo, and Mergangsan, samples are husband and postpartum primiparous mothers who breastfeed their babies which is 60, randomization techniques are used to divide the block into a treatment group and a control group of 30 samples each. Knowledge variables were measured with questionnaires before and after counseling. The variable of husband support in the questionnaire after counseling, while the variable of breastfeeding skills is observed with breasfeeding the checklist before and after counseling. Analysis of the data uses the Wilcoxon, Man Whitney and Spearman Rank.Result: The results showed the score of knowledge and skills in a group of couples and groups prior to the interven- tion itself not signiﬁcant (p> 0.05). The median value of knowledge for couples groups is 56.2, skills is 27, 27. The median value of the group itself to the knowledge is 55,0 27.27. The results of the knowledge, and skills after the in- tervention showed signiﬁcant differences (p< 0.05). Couples groups is knowledge median value is 92.5, the value of the skills is 100, while the value of the group’s own knowledge 88,7 and skills is 72.72. Median value of knowledge on husband support to couples is (88,8), higher than own group median value (72.2), there is a signiﬁcant difference(p < 0.05) . There is a husband and wife correlation knowledge which is signiﬁcant (p <0.05)Conclusion: There is an effect of breastfeeding on couples counseling to the increase of knowledge, support, and technical skills of breastfeeding in Yogyakarta city health centers. Knowledge, support, and technical skills about breastfeeding in a group of couples is higher than the group itself. Husband’s good knowledge can increase wife’s knowledge about proper breastfeeding techniques.